Experimental Investigation On The Performance Of Regeneration For Axial Flow Multilayer Silica Gel Hollow Cylinder Desiccant Bed - Wahab, Andyqa Abdul (Universiti Sains Malaysia, 2019)
The price and energy demand are getting higher from time to time. In order to cope with the climate change that taking place and to achieve the thermal comfort, this action will make people increase their dependency on consuming more energy. Solar cooling is a relatively new, reliable and clean energy application of proven refrigeration technology that able to improve comfort conditions. This technology also limits the impact on the environment and conserves energy. Advantage of the desiccant cooling technique is it avoids the refrigerants use that have a negative effect on the ozone layer. The main element in desiccant cooling system is the desiccator. In this study, single and double-layer hollow test bed were made. The adsorption ability of silica gels as the solid desiccant materials also tested under selected operating conditions. This research is designed also to examine the effect of air velocity effect on multilayer hollow cylindrical desiccant bed, filled with silica gel grains during regeneration process. For this purpose, measurements of temperature and humidity at the inlet and outlet of the test bed are done. However, the experimental setup requires a stable humidification capability for the adsorption experiment. There are several humidification methods are commonly used such as mist spray, evaporative, spray, and steam. Mist spray method is chosen to be applied for this project. This research brings various results related to humidification and regeneration process. The highest humidification effect is by using 2x4 vertical flow arrangement at 1 m/s with 89.8% of relative humidity followed by 83.7% in counter flow and 80.0% in parallel flow. While in regeneration view, humidity ratio is decreasing by 90% for single layer while 87.6% for double layer and for RH, it is decreasing by 94.6% for single layer while 90.5% for double layer. However, double layer gets more energy supplied by 1.4% which makes it more effective than single layer.